COVID-19 lockdown effects on water turbidity of a highly polluted lake in Dhaka city, Bangladesh - Nasher, N M Refat; Islam, Md. Yachin (National Geographical Journal of India, 2022)
Highly polluted lake water turbidity was analyzed to detect the changes during COVID-19 lockdown. Total eight Sentinel-2 Multispectral Instrument (MSI) and Landsat-8 Operational Land Imager (OLI) satellite imageries are used to observe the qualitative change of lake water turbidity for pre, during and post lockdown period. The imageries from January to June, and September and October were analyzed for change detections. Cloud free imageries have been chosen for analysis. The water pixels and turbidity are assessed by the Normalized Difference Water Index (NDWI) and Normalized Difference Turbidity Index (NDTI), respectively. The blue, red and NIR band reectance indicates that most of the lake water becomes clearer than before the lockdown period except May. The turbidity index shows low pollution after the lockdown period. High turbidity was observed evenly distributed from January to June. In September and October, high turbidity only found the upper part of the lake. This probably indicates the oating pollutants in the lake. The qualitative study of lake water turbidity using a remote sensing approach indicates that the COVID-19 lockdown improves the water quality in city lake water.